超臨界二氧化碳環境下添加聚丙烯纖維及含矽材料之套管水泥性質研究 - 張孟哲; Chang, Meng-Je (2022)
溫室效應所引起的氣候變化是自工業革命以來全球最重大的共同問題之ㄧ。為解決一直以來的碳排放問題，碳補集與封存技術中的地質封存法被認為是目前各國為達成淨零碳排放最具有可行性與潛力的技術之一。在二氧化碳注入地層中的過程中，通常會導致注入的二氧化碳與儲集層中存在的鹽水產生反應形成碳酸水，與水泥基質發生化學反應。這種化學反應改變了水泥的成分，並增加了其滲透性，這樣的過程我們稱之為碳化(Carbonation)，因為水泥體內部出現了微裂縫，最終使水泥結構損壞強度下降。 在過去的研究發現，添加含矽材料(例如:二氧化矽、碳化矽)以及聚丙烯纖維可增強API-G水泥性能，減緩水泥基質受到二氧化碳碳化造成的影響，並且增加力學強度。 本研究三種不同配比之添加物加入API-G水泥中，放入不同溫度、壓力(45°C、13.2MPa; 52°C、16.2MPa; 60°C、18.8MPa)之超臨界二氧化碳環境中反應0、7、14、28天，並在反應完成後進行物理特性(黏度試驗、滲透率試驗、密度試驗、超聲波試驗)、力學(單軸抗壓、巴西抗拉試驗)及微觀結構分析(SEM、EDS)，最後將各項試驗結果彙整後探討含有不同添加物之水泥在三種溫度壓力下的性質變化。 研究結果顯示，添加5wt.% SiO_2+0.125wt.%PPF的試體在三種配比中最能改善水泥性質，這是由於矽晶質填補孔隙使水泥的滲透性降低，防止二氧化碳侵蝕，並且因為聚丙烯纖維凝聚水泥基質，並因此提升了力學強度。 Climate change caused by the greenhouse effect is one of the most important common problems in the world since the industrial revolution. In order to solve the long-standing problem of carbon emissions, carbon capture and storage (CCS) technology is considered to be one of the most feasible and promising technologies for countries to achieve net zero carbon emissions. Carbon dioxide is captured and injected into the stratum, such as oil and gas layer, gas layer, and deep saline layer, etc. When CO2 is injected more than 800m underground, the temperature and pressure of the stratum will reach the critical point of its phase. The injection of CO2 into the formation usually results in a reaction between the injected CO2 and the brine present in the reservoir to form carbonic acid water, which reacts chemically with the cement matrix. This chemical reaction changes the composition of the cement and increases its permeability, a process we call carbonation, as microcracks appear within the cement body, eventually causing a loss of strength of the cement structure. Previous studies found that the addition of silica-containing materials (e.g., silica, silicon carbide) and polypropylene fibers could enhance the performance of API-G cement, mitigate the effects of carbonation on the cement matrix, and increase the mechanical strength. In this study, three different ratios of additives were added to API-G ...